THE PAMUGIH TRADITION IN MADURESE MARRIAGE CULTURE AND ITS IMPLICATIONS FOR THE SAKINAH FAMILY - U, Ubaidillah (At-Turost : Journal of Islamic Studies, 2023)
ABSTRACT Marriage can be said to be valid according to Islamic law if it fulfills the conditions and pillars of marriage. One of them is the existence of a dowry. However, Islam has never made it difficult for its people, such as the dowry that has been regulated in Islamic law. However, each region has its own customs where it is obligatory for a man to give more than a dowry, namely pamugih. In this study using a qualitative approach with valid data sources. After that, proceed with the analysis process. The analysis process is supported by a literature review which will then be presented in a descriptive form. While the results of this study show a comparison of the community's point of view about pamugih because according to one man, this pamugih is very burdensome because it is in the form of luggage such as contents of cupboards, mattresses, kitchen equipment etc. Exceeding the dowry given, however, a woman really agrees because they feel valued and responsible for a woman. The results of this study show the pros and cons, but these customs have been passed down from our ancestors and cannot be eliminated. Keywords: Pamugih, Culture, Implications